2014
DOI: 10.1186/1556-276x-9-229
|View full text |Cite
|
Sign up to set email alerts
|

Phytosynthesis of nanoparticles: concept, controversy and application

Abstract: Nanotechnology is an exciting and powerful discipline of science; the altered properties of which have offered many new and profitable products and applications. Agriculture, food and medicine sector industries have been investing more in nanotechnology research. Plants or their extracts provide a biological synthesis route of several metallic nanoparticles which is more eco-friendly and allows a controlled synthesis with well-defined size and shape. The rapid drug delivery in the presence of a carrier is a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
146
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(159 citation statements)
references
References 179 publications
(195 reference statements)
2
146
0
11
Order By: Relevance
“…It is identified that 15% of product on a global market is having some kind of nanotechnology incorporated during processing, and it is expected to reach US $ 1 trillion (Husen and Siddiqi 2014). There are several sources used for synthesis of nano particles such as, noble metals, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is identified that 15% of product on a global market is having some kind of nanotechnology incorporated during processing, and it is expected to reach US $ 1 trillion (Husen and Siddiqi 2014). There are several sources used for synthesis of nano particles such as, noble metals, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…AgNP's is unique among other metal nanoparticles and have received significant attraction among researchers because of their specific physical, chemical, and biological properties and their applications in medicine, cosmetics, and biomedical devices. Furthermore, AgNP's have been reported for antibacterial and antifungal activities [16]. It also possesses low toxicity when compared to other nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that in the near future over 15 % of all products at the world market will certainly include nanotechnology in their production process [37]. Designed nanoparticles (1 to 100 nm) may possess different physical and chemical properties than those found in nature; and their impact on human health must be evaluated based on their size and shape [27,49,62,88].…”
Section: Abstract: Nanoparticles Cerium Dioxide Biotransformation mentioning
confidence: 99%